2014
DOI: 10.1245/s10434-014-3766-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Hepatic Arterial Infusion Chemotherapy Using 5-Fluorouracil and Systemic Pegylated Interferon α-2b for Advanced Intrahepatic Cholangiocarcinoma

Abstract: The combination therapy of PEG-IFNα-2b and 5-FU for advanced ICC seems not to be worse than the results of the previous studies. Furthermore, most adverse effects are transient and well tolerated. Based on the present findings, this combination therapy may be useful for patients with advanced ICC as one of the therapeutic option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…Of note, 16 of these studies assessed the safety and efficacy of FDA-approved cytokines (i.e., G-CSF, GM-CSF, IFN-a2a, IFN-a2b and IL-2) as off-label immunostimulatory interventions, [98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] while only one trial tested the clinical profile of a hitherto experimental cytokine (i.e., IL-15). 114 The safety and efficacy of G-CSF have been assessed in 11 breast carcinoma patients, who were treated with subcutaneous G-CSF in combination with 5-fluorouracil (5-FU), epirubicin, cyclophosphamide and paclitaxel (NCT02225652).…”
Section: Update On the Development Of Recombinant Cytokines As Immunomentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, 16 of these studies assessed the safety and efficacy of FDA-approved cytokines (i.e., G-CSF, GM-CSF, IFN-a2a, IFN-a2b and IL-2) as off-label immunostimulatory interventions, [98][99][100][101][102][103][104][105][106][107][108][109][110][111][112][113] while only one trial tested the clinical profile of a hitherto experimental cytokine (i.e., IL-15). 114 The safety and efficacy of G-CSF have been assessed in 11 breast carcinoma patients, who were treated with subcutaneous G-CSF in combination with 5-fluorouracil (5-FU), epirubicin, cyclophosphamide and paclitaxel (NCT02225652).…”
Section: Update On the Development Of Recombinant Cytokines As Immunomentioning
confidence: 99%
“…98 The safety and efficacy of IFN-a2a and IFN-a2b have been evaluated in (1) five cohorts of 791, 365, 53, 51 and 40 subjects with advanced RCC, who received IFN-a2a in combination with the FDA-approved tumor-targeting antibody bevacizumab (which neutralizes vascular endothelial growth factor A, VEGFA) [121][122][123] (NCT00719264), along with the multitarget tyrosine kinase inhibitor sorafenib (UMIN000002466), 124,125 in the context of a multimodal treatment involving potentially immunogenic chemotherapy plus bevacizumab i.v. and low dose IL-2 s.c., [126][127][128] ; or optionally combined with a trophoblast glycoprotein (TPBG)-redirected variant of staphylococcal enterotoxin A (naptumomab estafenatox); 100,105,108,113,129 (2) 313 patients with symptomatic indolent B-cell lymphoma, receiving IFN-a2a in combination with the CD20-targeting mAb rituximab 130,131 99 Cumulatively, these studies confirm that IFNa2a and IFN-a2b can be safely administered to cancer patients as off-label indications. IFN-a2a improved the clinical efficacy of sorafenib-based chemotherapy for advanced RCC, 113 but failed to do so better than the mechanistic target of rapamycin (MTOR) inhibitors everolimus or temsirolimus 132,133 (although it was associated with a lower incidence of side effects) in patients with metastatic RCC co-treated with bevacizumab, 108,129 as it failed to ameliorate the therapeutic profile of rituximab in indolent B-cell lymphoma patients.…”
Section: Update On the Development Of Recombinant Cytokines As Immunomentioning
confidence: 99%
“…Hepatic arterial infusion chemotherapy (HAIC)-injecting chemotherapeutic agents into the hepatic artery without embolization-reduces the systemic side effects seen with systemic chemotherapy ( 13 ). Previous studies have illustrated that HAIC is a promising option for advanced ICC and has shown higher tumor control rates than systemic chemotherapy ( 14 ). Chemotherapy with hepatic intraarterial epirubicin and cisplatin combined with systemic 5-fluorouracil (5-FU) was used in patients with unresectable ICC, and the objective response rate and median survival time were 36% and 15.4 months, respectively ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Combination of weekly pegylated interferon α-2b and intra-arterial infusion of 5-FU has been shown to confer 1-year survival rate of 54% and median survival of almost 15 months in a recent study. 145 The recent phase I/II study from Japan showed that gemcitabine infusion was associated with tumor response of 8%, with neutropenia being the major side effect of this treatment. HAI has been reported with 5-FU-based regimens and has shown effectiveness, but large trials are lacking.…”
Section: Hepatic Artery-based Therapiesmentioning
confidence: 99%